Effects of Passive and Active Decontamination on Metal Materials Contaminated by Sulphur Mustard (Yperite) - Marketa Weisheitelova; Karel Klouda; Stanislav Lasek (Communications - Scientific letters of the University of Zilina, 2019)
This paper reports the results of the experimentally determined effects of decontaminating agents on metal surfaces resulting from passive and active decontamination after sulphur mustard (Yperite) contamination. The paper includes an analysis of the experimentally obtained results for each metal (Zinc, Nickel, Aluminium, Brass, Steel, Copper).